Energy-efficient relaxed rekeying policies for distributed key management in sensor networks. (10th December 2008) - Jibi, Abraham; Ramanatha, K.S.
In this paper, we discuss a basic key management protocol to generate and distribute the keys required for a secure group communication system, which also preserves the backward and forward secrecies. We devise a few relaxed policies for rekeying and formulate an enhanced set of protocols for key management. All the communications in the protocols are properly authenticated using Elliptic Curve Digital Signature scheme. The relaxed protocols reduce the number of rekeying to almost 25%, thus saving energy. The security analysis shows that our protocols can withstand several possible security attacks especially the serious one, the node capture attack.